ECOLOGICAL RELATIONSHIPS BETWEEN ENDOPARASITES AND THE FISH SALMINUS BRASILIENSIS (CHARACIDAE) IN A NEOTROPICAL FLOODPLAIN - Cucolo Karling, Letícia (2013)
The present study was designed to characterize the community structure of parasites of Salminus brasiliensis in the upper Paraná River during different seasons, and to examine the levels of parasitism of this hosts. The community of parasites of S. brasiliensis did not have a dominant species. Four of the five most prevalent parasite species showed aggregate distribution. In relation to other aspects of the community, each group encompassed their particular parasite, which highlights the differences inherent in the biology and life cycle of each species.